Organizing NORTHCOM for Success: A Theater Special Operations Command - McGillis, Gay M. (2003)
A Theater Special Operations Command (SOC), a sub-unified command, advises combatant commanders on the capabilities of Special Operations Forces (SOF), provides SOF for employment, and integrates SOF fully into theater plans by planning, coordinating, conducting, and supporting the geographical unified commander. The SOC is a trained and resourced rapid deployment joint task force headquarters, if needed. The new unified command, U.S. Northern Command (NORTHCOM), attained initial operations capability (IOC) on October 1, 2002. NORTHCOM is not organized for success to accomplish its new mission of homeland defense and civil support. NORTHCOM must transform to an organization that can anticipate and adapt to its new missions. By analyzing the planning, command and control, and coordination of SOF support during Hurricane Andrew and the 1996 Atlanta Olympics, it was determined that a SOC would be a critical component to this new organization. The SOC will be vital during both deliberate and crisis action planning, advising on the best method to integrate SOF capabilities. Early planning efforts by SOCOM for SOF support to JTF-Olympics determined only a small JSOTF was needed to coordinate with the lead federal agency for counterterrorism, the FBI. In contrast, JTF-Andrew did not have a Special Operations Coordination element and had to learn the capabilities and limitations of SOF before being able to employ them effectively for the disaster relief efforts. This was a problem in the time-sensitive environment of a massive hurricane recovery operation. SOCNORTH would ensure SOF are integrated into any operational plan, so they can assist NORTHCOM responses to any future homeland crises. SOCNORTH would advise the NORTHCOM commander and ensure SOF are synchronized, coordinated, and deconflicted in any operation assigned to NORTHCOM.